2011
DOI: 10.1021/am200425y
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Reduction of CO2 Using TiO2: Effects of Organic Adsorbates on TiO2 and Deposition of Pd onto TiO2

Abstract: Reduction of CO(2) using semiconductors as photocatalysts has recently attracted a great deal of attention again. The effects of organic adsorbates on semiconductors on the photocatalytic products are noteworthy. On untreated TiO(2) (P-25) particles a considerable number of organic molecules such as acetic acid were adsorbed. Although irradiation of an aqueous suspension of this TiO(2) resulted in the formation of a significant amount of CH(4) as a major product, it was strongly suggested that its formation ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
239
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(255 citation statements)
references
References 79 publications
13
239
0
3
Order By: Relevance
“…Second, electron transfer could be promoted in the direction from TiO 2 CB to external trappers or carriers. The electron trappers can be noble metals (e.g., Pt, Pd, Au, Ag) (Sasirekha et al, 2006;Iizuka et al, 2011;Yui et al, 2011;An et al, 2012;Uner and Oymak, 2012;Wang et al, 2012b) or metal oxides (e.g., CuO, FeO x , CeO 2 ) (Tseng et al, 2004;Qin et al, 2011;Srinivas et al, 2011;Wang et al, 2011b;Truong et al, 2012;Zhao et al, 2012b), and the electron carriers are often carbon materials (e.g., graphene) (Liang et al, 2011(Liang et al, , 2012Tu et al, 2012). Third, the incorporation of TiO 2 with another semiconductor, i.e., photo-sensitizer (e.g., AgBr, CdSe, PbS) Asi et al, 2011;Wang et al, 2011a;An et al, 2012) or n-type semiconductor (e.g., ZnO) (Xi et al, 2011), promotes electron transfer between the CB of the second semiconductor and the CB of TiO 2 .…”
Section: Effect Of Materials Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, electron transfer could be promoted in the direction from TiO 2 CB to external trappers or carriers. The electron trappers can be noble metals (e.g., Pt, Pd, Au, Ag) (Sasirekha et al, 2006;Iizuka et al, 2011;Yui et al, 2011;An et al, 2012;Uner and Oymak, 2012;Wang et al, 2012b) or metal oxides (e.g., CuO, FeO x , CeO 2 ) (Tseng et al, 2004;Qin et al, 2011;Srinivas et al, 2011;Wang et al, 2011b;Truong et al, 2012;Zhao et al, 2012b), and the electron carriers are often carbon materials (e.g., graphene) (Liang et al, 2011(Liang et al, , 2012Tu et al, 2012). Third, the incorporation of TiO 2 with another semiconductor, i.e., photo-sensitizer (e.g., AgBr, CdSe, PbS) Asi et al, 2011;Wang et al, 2011a;An et al, 2012) or n-type semiconductor (e.g., ZnO) (Xi et al, 2011), promotes electron transfer between the CB of the second semiconductor and the CB of TiO 2 .…”
Section: Effect Of Materials Modificationmentioning
confidence: 99%
“…It was proposed that the energy for band separation of the smaller Pt particles was higher due to the quantum confinement, thus preventing electron transfer from TiO 2 CB to Pt. Yui et al (2011) suggested that the addition of Pd to TO 2 induced the reduction of CO 2 to CH 4 , while the oxidation of Pd to PdO caused the catalyst deactivation. The above studies indicate the importance of choosing an appropriate noble metal, tailoring the particle size in an appropriate range, and avoiding the oxidation of noble metal to metal oxide.…”
Section: Electron Transfer From the Impurity State To Tio 2 Cbmentioning
confidence: 99%
“…The organic adsorbed on the surface of TiO 2 could participate in a so-called photo-Kolbe reaction (CH 3 COOH, for example) [36] :…”
Section: Key Points Of the Experimental Detailsmentioning
confidence: 99%
“…Because of its band gap of 3.2 eV, TiO 2 is activated only by ultraviolet (UV) light (wavelength<387 nm). Pure TiO 2 can't be effectively activated under solar light irradiation, which limits its practical application, because UV light just accounts for less than 5 % of the solar energy that reaches the surface of the earth [12][13][14]. In recent years, visible light responsive photocatalysts have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%